Antifungal mechanism of action of Schinus lentiscifolius Marchand essential oil and its synergistic effect in vitro with terbinafine and ciclopirox against dermatophytes. (28th June 2018) - Danielli, Letícia J.; Pippi, Bruna; Duarte, Jonathaline A.; Maciel, Ana J.; Lopes, William; Machado, Michel M.; Oliveira, Luis Flávio S.; Vainstein, Marilene H.; Teixeira, Mário L.; Bordignon, Sérgio A. L.; Fuentefria, Alexandre M.; Apel, Miriam A.
Abstract: Objectives: The aim of this study was to evaluate the antifungal, antichemotactic and antioxidant activities of Schinus lentiscifolius essential oil, as well as its combined effect with terbinafine and ciclopirox, against dermatophytes. Methods: Essential oil was analysed by GC‐MS. The antifungal activity and the mechanism of action were determined by broth microdilution, sorbitol and ergosterol assays, as well as scanning electron microscopy. The checkerboard method was used for evaluating the interactions with commercial antifungal agents. The antioxidant and antichemotactic activities were measured using the DPPH and the modified Boyden chamber methods, respectively. Key findings: Chemical analysis revealed the presence of 33 compounds, the primary ones being γ‐eudesmol (12.8%) and elemol (10.5%). The oil exhibited 97.4% of antichemotactic activity and 37.9% of antioxidant activity. Antifungal screening showed effect against dermatophytes with minimum inhibitory concentration values of 125 and 250 μg/ml. Regarding the mechanisms of action, the assays showed that the oil can act on the fungal cell wall and membrane. Synergistic interactions were observed using the combination with antifungals, primarily terbinafine. Conclusions: Schinus lentiscifolius essential oil acted as a chemosensitizer of the fungal cell to the drug, resulting in an improvement in the antifungal effect. Therefore, this combination can be considered as an alternative for the topical treatment of dermatophytosis.